Generating enabling conditions to strengthen a research-rich teaching profession: lessons from an Australian study. Issue 1 (2nd January 2021) - White, Simone
ABSTRACT: The increasing datafication of teachers' work and schooling practices as evidenced through various metrics of student testing and school improvement measures have continued to grow unabated across many OECD Countries. Such practices have been fuelled by global competition for league tables such as the Programme for International Student Assessment (PISA) with 'big data' having a major impact on how teachers are expected to gather, analyse and report data. For schools in Australia, the turn of the millennium has heralded the 'high stakes' data trend and the roll-out of standardised testing. This paper reports on an Australian study's findings, against such a backdrop, to explore the impact and challenges of an overly data-rich environment for educators, teachers and system leaders and what might be the enabling conditions to move towards a more research-rich teaching profession. The findings suggest that perhaps standards and data are not the enemy for teachers, rather it is standardisation and the datafication of students that creates an amplification of the effects of institutional rankings and league tables. Enabling conditions are offered to adopt a more comprehensive and inclusive view of what counts as research and who conducts research, key to enabling a mature teaching profession.